2018
DOI: 10.1080/19420862.2018.1451288
|View full text |Cite
|
Sign up to set email alerts
|

Functional domain analysis of SOX18 transcription factor using a single-chain variable fragment-based approach

Abstract: Antibodies are routinely used to study the activity of transcription factors, using various in vitro and in vivo approaches such as electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, genome-wide method analysis coupled with next generation sequencing, or mass spectrometry. More recently, a new application for antibodies has emerged as crystallisation scaffolds for difficult to crystallise proteins, such as transcription factors. Only in a few rare cases, antibodies have been used to modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…In addition, they found that chemical modifications to SM4 dramatically changed its PPI disrupting capacity, opening the door to fine-tuning of SOX18 activity [130]. In line with this, they reported that antibodies and antibody fragments could be used to modulate transcriptional output [131].…”
Section: Sox18mentioning
confidence: 78%
“…In addition, they found that chemical modifications to SM4 dramatically changed its PPI disrupting capacity, opening the door to fine-tuning of SOX18 activity [130]. In line with this, they reported that antibodies and antibody fragments could be used to modulate transcriptional output [131].…”
Section: Sox18mentioning
confidence: 78%
“…Phage particles were purified from the culture supernatant by two rounds of PEG/NaCl precipitation as described elsewhere. 55 The phage titer was determined by infecting an exponentially growing E. coli XL1-blue culture with serial dilutions of purified library phage. Infected bacteria were plated on 2YT-AmpGlu plates and colonies were counted following overnight incubation at 37 °C.…”
Section: ■ Methodsmentioning
confidence: 99%
“…One round of biopanning was performed against EGFR-His as described previously. 55 In brief, immunotubes (Nunc Maxisorp, Thermo Fischer Scientific) were coated overnight with 2 × 10 μg interleukin 22-His (negative antigen) and 10 μg EGFR-His (positive antigen) followed by a series of washes with PBS. The tubes were blocked with 1% casein in PBS (CPBS) for 1 h at room temperature (RT).…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HMG-box is present in all groups of SOX proteins (A-H, 20 SOX) and is classically used as a reference to align and compare these proteins since this region is highly conserved ( 7 ). It is made up of 3 α-helixes, whereby α1 and α2 are involved with DNA binding while α3 is involved in protein-protein interactions ( 13 ). The HMG-box recognizes a heptameric consensus sequence (5-A/TA/TCAAA/TG-3) on the DNA.…”
Section: Introductionmentioning
confidence: 99%